2014
DOI: 10.1007/s10709-014-9798-x
|View full text |Cite
|
Sign up to set email alerts
|

Sequence analysis of the Ras-MAPK pathway genes SOS1, EGFR & GRB2 in silver foxes (Vulpes vulpes): candidate genes for hereditary hyperplastic gingivitis

Abstract: Hereditary hyperplastic gingivitis (HHG) is an autosomal recessive disease that presents with progressive gingival proliferation in farmed silver foxes. Hereditary gingival fibromatosis (HGF) is an analogous condition in humans that is genetically heterogeneous with several known autosomal dominant loci. For one locus the causative mutation is in the Son of sevenless homologue 1 (SOS1) gene. For the remaining loci, the molecular mechanisms are unknown but Ras pathway involvement is suspected. Here we compare s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Furthermore, our network also shows the close relationship among GRB2, EGFR, and PTPN11 pathways (Figure 9), which is accordant with previous reports [68, 69] except of PTPN11 pathway. Further work is needed to confirm the detailed relation among the three pathways.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, our network also shows the close relationship among GRB2, EGFR, and PTPN11 pathways (Figure 9), which is accordant with previous reports [68, 69] except of PTPN11 pathway. Further work is needed to confirm the detailed relation among the three pathways.…”
Section: Discussionsupporting
confidence: 92%
“…HRAS also acts as a molecular switch in processes of the cell proliferation, differentiation, survival, and death . GRB2 is also a key regulator in RAS signaling . Two MAPK related proteins, MAPK3 and MAPK9, were also found in the PknG–human protein interaction network.…”
Section: Resultsmentioning
confidence: 99%
“…[30] GRB2 is also a key regulator in RAS signaling. [31] Two MAPK related proteins, MAPK3 and MAPK9, were also found in the PknG-human protein interaction network. The MAPK1/3 pathway is activated by extracellular and intracellular mitogenic stimuli and has crucial roles in cellular differentiation, proliferation, and survival.…”
Section: Key Biological Functions Were Enriched In the Pkng-human Promentioning
confidence: 99%
“…These have functions as molecular switches for signaling pathways regulating cell proliferation, survival, migration, differentiation and cytoskeletal dynamism. 34 However, in reality, many other proteins are also involved in this pathway, including EGFR, 35 GRB2, 36 and VEGF and the PDGF family. 37, 38 A number of researchers have demonstrated that upon stimulation with growth factors, or other inputs, the Ras/MAPK system can promote cell proliferation, differentiation and/or migration.…”
Section: Discussionmentioning
confidence: 99%